Réception télévisuelle et resocialisation des immigrants d’origine tunisienne à la société québécoise - Seima Souissi (Communiquer, 2018)
This article is based on a doctoral research on the television’s contribution to the resocialization of immigrants from Tunisian origins newly established in Quebec. The results of this research, which addresses intercultural communication in a migratory context from the construction of the television content’s meaning, reveal that television viewing exposes immigrants to a completely new universe and difficult to understand. Therefore, at the beginning of the stay, television is rarely mobilized as a way of resocialization and television viewing is rather a component of the immigration experience. Its use and effects merge with the social experiences of immigrants who have not been exposed to local television products before arriving in Quebec. Immigrants of Tunisian origin, more exposed to the French, American or Arab television products that are accessible in Tunisia, apprehend the contents of Quebec television in the light of their multiple television culture. They note that Quebec television stands out for its “Quebecocentrism”, while being strongly influenced by American standards.